Implementasi User Centered Design dan Reporting Services Pada Sistem Informasi Laporan Izin dan Kinerja Siswa Pada Sekolah Umum - Irawan, Dika; Darusalam, Ucuk (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Discipline is one of the significant points in building education, especially at SMP NEGERI 20 DEPOK. The school picket officer is tasked with processing books, second recording student attendance, student permits, and student performance reports at SMP Negeri 20 Depok. Computer-based information systems also have an important role in supporting the school to carry out teaching and learning activities optimally. The Picket Officer Daily Report Information System is designed using Sublime Text 3 tools and uses a MySQL database. While the programming languages used are HTML, CSS and PHP using the waterfall method which will take data from SMP Negeri 20 Depok. Based on the retrieval of information carried out, the Daily Report Information System is designed to assist the processing of all student activities such as student attendance, student permits and student performance reports. The Picket Officer report information system helps process data efficiently and maximally both in terms of time and materials used, where so far the daily reports of picket officers at SMP Negeri 20 Depok are still done conventionally.